(untitled) (International Journal of Ayurveda and Pharma Research, 2020)
Vruna is the commonest problem we face in practice. The wound in and out itself is the biggest challenge to medical practitioners, even more, when it’s a non-healing type. In practice, Dushta vrana is that the most typically encountered problem faced by a health professional. Wound healing is a major problem in surgical practice also. Acharya Sushruta, has explained Vrana very well in “Sushruta Samhita” as a concourse of wound healing procedures described by Sushruta still holds its place today. Sushruta has described Shashti Upakrama (60 measures) for the great management of Vruna (wound). Here is a case report- of 57 Years male presented with complaints of an ulcer/ non healing wound on medial aspect and on lateral malleolus of right foot with pain, discharge, foul smell, edema, discoloration, and pus discharge. The case was treated with Vruno-heal oil as local application, and with few internal medications. Among these 60 Upakramas - Parisheka, Lekhana, Kashaya, Mrudukarma, Bandha modalities were used to treat the wound.